Valor biológico de las proteínas contenidas en el producto comercial ensure utilizado en terapia nutricional farmacológica - Valverde Quispe, Grace Joan (2016)
In this research the biological value of proteins Ensure commercial product, used in nutritional therapy pharmacological, using the biological method of net protein utilization (NPU), for it was used Rattus rattus var. norvegicus, of 33-57 days old and 50-60 g in weight. A group aproteic based diet and the other group the food under study was administered, the results were: digestibility 95,98 %, NPU 8,22 % and biological value of 87,66 %. An analysis of the results it is concluded that every 100 g of Protein Ensure commercial product, the body assimilates 88 g.